Inflation accounting : report of the Inflation Accounting Committee - Sandilands, F.E.P (London : Her Majesty's Stationery Office, 1975)
This work consists of 300 written submissions received not only from the country but also from oversea countries. Surveys of UK companies were also carried out to supplement the written submissions.
"Presented to Parliament by the Chancellor of the Exchequer and the Secretary of State for Trade by command of Her Majesty, September 1975."
Includes bibliographical references.
osc 7/11/17
Loans
Keywords: Accounting; Inflation